IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN BAHASA INDONESIA PADA FASE F SMA NEGERI 6 SOLOK SELATAN - Ambar Wati; Dewi Anggraini (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This study aims to analyze and describe the planning and implementation of the implementation of the Merdeka curriculum in learning Indonesian in Phase F at SMA Negeri 6 Solok Selatan. This study uses a qualitative approach with a descriptive method. The data in this study are primary and secondary data. The data sources used include teaching modules, Indonesian language teachers, interview results with Indonesian language teachers who teach in Phase F, especially class XI F5, and curriculum representatives. The research instrument is self-research. The results of the study indicate that the planning of the implementation of the Merdeka curriculum in learning Indonesian has been well prepared, including the preparation of appropriate teaching tools and learning strategies. In addition, the implementation of the curriculum has been carried out in accordance with the learning model applied. Thus, it can be concluded that the planning and implementation of the Merdeka curriculum in learning Indonesian in Phase F at SMA Negeri 6 Solok Selatan have been carried out optimally.